Chromatographic fingerprint analysis for determining the presence of vitexin and isovitexin on seven varieties of ficus deltoidea - Zunoliza Abdullah (Universiti Pendidikan Sultan Idris, 2018)
Chromatographic fingerprint analysis for determining the presence of vitexin and isovitexin on seven varieties of ficus deltoidea by Zunoliza Abdullah